2009
DOI: 10.1152/ajpheart.00372.2008
|View full text |Cite
|
Sign up to set email alerts
|

Role of heme oxygenase-1 in the cardioprotective effects of erythropoietin during myocardial ischemia and reperfusion

Abstract: of heme oxygenase-1 in the cardioprotective effects of erythropoietin during myocardial ischemia and reperfusion. Am J Physiol Heart Circ Physiol 296: H84 -H93, 2009; doi:10.1152/ajpheart.00372.2008.-We have recently demonstrated that erythropoietin (EPO) protects cardiomyocytes from apoptosis during myocardial ischemia-reperfusion (I/R). The objective of the present study was to investigate the role of heme oxygenase (HO)-1 in the antiapoptotic effects of EPO. Primary cultures of neonatal mouse cardiomyocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 54 publications
4
23
0
Order By: Relevance
“…This implies that upregulation of AQP4 by EPO binding to EPOR may result from activation of JNK and p38-MAPK signal transduction pathways, which are known to be activated by EPO. [34][35][36] Several previous studies reported that a p38-MAPK inhibitor suppressed AQP4 upregulation induced by manganese treatment or hyperosmotic solutions. 16,17 Moreover, our recent study reveals that the JNK pathway was involved in VEGF's effect on AQP4 upregulation.…”
Section: Erythropoietin Protects Bbb From Disruptionmentioning
confidence: 99%
“…This implies that upregulation of AQP4 by EPO binding to EPOR may result from activation of JNK and p38-MAPK signal transduction pathways, which are known to be activated by EPO. [34][35][36] Several previous studies reported that a p38-MAPK inhibitor suppressed AQP4 upregulation induced by manganese treatment or hyperosmotic solutions. 16,17 Moreover, our recent study reveals that the JNK pathway was involved in VEGF's effect on AQP4 upregulation.…”
Section: Erythropoietin Protects Bbb From Disruptionmentioning
confidence: 99%
“…152 The stromal cell-derived factor-1α activates chemokine receptor 4 and reduces IS on exogenous administration, 153 and stromal cell-derived factor-1α is causally involved in IS reduction by RIPC. 154 Exogenous erythropoietin reduces IS when given before ischemia, 155 but also when given before reperfusion 156,157 with involvement of phosphatidylinositol (4,5)-bisphosphate 3-kinase (PI3K), ERK, p38, and heme oxy genase, but there is no evidence that erythropoietin is causally involved in the conditioning phenomena.…”
Section: Cytokines/chemokinesmentioning
confidence: 99%
“…protective responses may harness HO-1 (1,5,63). We find that I=R rapidly induces HO-1 mRNA and tissue activity (within 45 min), an effect exaggerated by A 1 AR deletion (Fig.…”
mentioning
confidence: 99%